Density-Dependent Prevalence of Francisella tularensis in Fluctuating Vole Populations, Northwestern Spain - Ruth Rodríguez-Pastor; Raquel Escudero; Dolors Vidal; François Mougeot; Beatriz Arroyo; Xavier Lambin; Ave Maria Vila-Coro; Isabel Rodríguez-Moreno; Pedro Anda; Juan J. Luque-Larena (Emerging Infectious Diseases, 2017)
Tularemia in humans in northwestern Spain is associated with increases in vole populations. Prevalence of infection with Francisella tularensis in common voles increased to 33% during a vole population fluctuation. This finding confirms that voles are spillover agents for zoonotic outbreaks. Ecologic interactions associated with tularemia prevention should be considered.